2022
DOI: 10.1177/15459683221129274
|View full text |Cite
|
Sign up to set email alerts
|

Vagus Nerve Stimulation Paired With Rehabilitation for Upper Limb Motor Impairment and Function After Chronic Ischemic Stroke: Subgroup Analysis of the Randomized, Blinded, Pivotal, VNS-REHAB Device Trial

Abstract: Background Vagus Nerve Stimulation (VNS) paired with rehabilitation improved upper extremity impairment and function in a recent pivotal, randomized, triple-blind, sham-controlled trial in people with chronic arm weakness after stroke. Objective We aimed to determine whether treatment effects varied across candidate subgroups, such as younger age or less injury. Methods Participants were randomized to receive rehabilitation paired with active VNS or rehabilitation paired with sham stimulation (Control). The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Nor have studies provided direct clinical evidence for the benefits of pairing taVNS with movement by decoding EMG signals during motor training. Previous studies have indicated that pairing VNS (10)(11)(12) or taVNS (27,28,30) 27) highlighted the benefits of movement-synchronized taVNS by decoding EMG signals compared to simple combination of taVNS and movements. However, their study was not designed with a sham control group and the number of subjects per group was limited to less than 10.…”
Section: Expected Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nor have studies provided direct clinical evidence for the benefits of pairing taVNS with movement by decoding EMG signals during motor training. Previous studies have indicated that pairing VNS (10)(11)(12) or taVNS (27,28,30) 27) highlighted the benefits of movement-synchronized taVNS by decoding EMG signals compared to simple combination of taVNS and movements. However, their study was not designed with a sham control group and the number of subjects per group was limited to less than 10.…”
Section: Expected Results and Discussionmentioning
confidence: 99%
“…Nor have studies provided direct clinical evidence for the benefits of pairing taVNS with movement by decoding EMG signals during motor training. Previous studies have indicated that pairing VNS ( 10 12 ) or taVNS ( 27 , 28 , 30 ) with rehabilitative training can enhance motor function recovery. Whereas a study by Wu et al ( 31 ) demonstrated that taVNS treatment prior to regular motor training could improve motor functions.…”
Section: Expected Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VNS-REHAB study subgroup analysis indicated no significant difference in the mean FMA-UE score improvement in subgroups divided by age (<62 versus ≥62), sex, stroke severity (FMA-UE score ≤34 versus >34), time since stroke (≤2 years versus >2 years), side of paresis, or presence/absence of cortical involvement. 67 These results are promising that invasive VNS paired with rehabilitation is potentially beneficial to a variety of stroke patients. Furthermore, the VNS-REHAB study did not include individuals with very severe strokes (FMA-UE <20), infratentorial stroke, intracerebral hemorrhage or those with multiple infarcts.…”
Section: Target Populationsmentioning
confidence: 88%
“…This pathway can also be activated via non-invasive Vagus Nerve Stimulation (nVNS) [ 15 ], which could turn out to be a true game changer not only in etiologic rehabilitation [ 16 ] but also in symptomatic rehabilitation, notably acting on motor rehabilitation [ 17 ] and pain [ 18 ].…”
Section: Discussionmentioning
confidence: 99%